Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/jpm10030074
|View full text |Cite
|
Sign up to set email alerts
|

The Viral Hypothesis in Alzheimer’s Disease: Novel Insights and Pathogen-Based Biomarkers

Abstract: Early diagnosis of Alzheimer’s disease (AD) and the identification of significant risk factors are necessary to better understand disease progression, and to develop intervention-based therapies prior to significant neurodegeneration. There is thus a critical need to establish biomarkers which can predict the risk of developing AD before the onset of cognitive decline. A number of studies have indicated that exposure to various microbial pathogens can accelerate AD pathology. Additionally, several studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…Interestingly IL-10 was also increased in SMC and AD, but not in MCI, suggesting that the inflammatory state was not balanced by an anti-inflammatory production [ 159 ]. Considering an eventual infectious origin of the disease [ 160 162 ] we have used an extract from Pg, the cornerstone bacteria involved in periodontitis and in AD, in addition to traditional LPS [ 13 , 163 ]. The obtained results were quite similar for both stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly IL-10 was also increased in SMC and AD, but not in MCI, suggesting that the inflammatory state was not balanced by an anti-inflammatory production [ 159 ]. Considering an eventual infectious origin of the disease [ 160 162 ] we have used an extract from Pg, the cornerstone bacteria involved in periodontitis and in AD, in addition to traditional LPS [ 13 , 163 ]. The obtained results were quite similar for both stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Worthy of attention is the fact that a large number of studies have indicated that exposure to various microbial pathogens, viruses, in particular, can accelerate Dementia pathology, suggesting that certain types of infections may play a significant role in Alzheimer's pathogenesis. This is important data because if viral infections increase the risk of AD, the viruses themselves represent a modifiable risk factor that can be treated with the therapeutic intervention [ 40 ].…”
Section: How Does the Sars-cov-2 Virus Affect The Brain?mentioning
confidence: 99%
“…Multiple independent laboratories continue to report the detection of viral, bacterial, fungal, protozoal, or other microbially-derived nucleic acid sequences or neurotoxins, such as highly inflammatory bacterial amyloid peptides, lipopolysaccharide (LPS), and many microbe-derived endotoxins within AD affected brain tissues [ 24 , 29 , 34 , 36 , 39 , 40 ]. Microbial biomarkers and systems biology approaches to understand host–microbiome interactions have been suggested by multiple AD researchers that both: ( i ) predict the risk of developing AD well before the onset of cognitive decline; and ( ii ) stimulate and/or accelerate the development of classical AD neuropathology [ 24 , 34 , 39 , 41 , 42 , 43 , 44 ].…”
Section: Novel Emerging and Advanced Diagnostic Biomarkers For Amentioning
confidence: 99%
“…Whether these viral, bacterial, or other microbial DNA- or RNA-based nucleic acids or associated lipoproteins, liposaccharides, peptidoglycans, bacterial-derived amyloids, and/or neurotoxins originate from the gastrointestinal (GI) tract microbiome, a potential brain microbiome, or some dormant pathological microbiome is currently not well understood [ 24 , 35 , 36 , 40 , 43 , 45 ]. Since 1978, at least ~4400 peer-reviewed research articles provide convincing evidence that multiple species of microbes, including viruses, bacteria (especially Gram-negative bacteria), and other microorganisms or their secreted components are strongly associated with the onset and/or the development of AD-type change [ 24 , 29 , 33 , 34 , 41 , 42 , 43 , 46 ]. If microbial presence in the brain is involved in the early initiation or propagation of AD, as currently suspected, then specialized RNA-sequencing applications or nucleic acid-containing gene chips, electrochemical biosensors, or panels of microbial-derived 16S ribosomal RNA (rRNA) interrogated with nucleic acid probes derived from AD biofluids might be useful as novel AD biomarkers in the detection of microbial patterns of expression from human brain tissues at any stage or degree of AD neuropathology.…”
Section: Novel Emerging and Advanced Diagnostic Biomarkers For Amentioning
confidence: 99%